THE EFFECT OF MARKETING STRATEGY ON CUSTOMER SATISFACTION AT PT KENCANA MULIA ABADI - Herlin Cahyani Mendrofa; Otanius Laia; Kurniawan Sarototonafo Zai; Yupiter Mendrofa (LPPM YPITI, 2026)
This study aims to determine the effect of marketing strategies on customer satisfaction at PT Kencana Mulia Abadi in Gunugsitoli City. The background of this study is based on the importance of implementing appropriate marketing strategies to increase customer satisfaction and loyalty. In this study, marketing strategies are analyzed based on the marketing mix elements implemented by the company, while customer satisfaction is measured through the conformity of expectations, repurchase intention, and willingness to recommend. This study uses a quantitative approach with an instrument in the form of a questionnaire distributed to 50 respondents who are customers of PT Kencana Mulia Abadi. Data analysis techniques used include validity tests, reliability, simple linear regression, and hypothesis testing. The results of the study indicate that marketing strategies have a positive and significant effect on customer satisfaction, with a t-test value of 7.833 and a significance of 0.000 <0.05. In addition, a coefficient of determination (R²) value of 0.561 is obtained, which means that 56.1% of the variation in customer satisfaction is influenced by marketing strategies, while the remaining 43.9% is influenced by other factors outside this study. Thus, the better the marketing strategy implemented, the more customer satisfaction at PT Kencana Mulia Abadi will increase. This research is expected to be a material for evaluation and consideration for the company in compiling and developing more effective marketing strategies in the future.